Emotional Self-Care: Exploring the Influencing Factors Among Individuals With Cancer - Sebastian, Ann Tresa; Rajkumar, Eslavath; John, Romate; Daniel, Monica; George, Allen Joshua; Greeshma, Rajgopal; James, Treasa (Frontiers in Psychology, 2022)
Cancer is a leading source of distress and fatality worldwide. Cancer-related aberrant cell proliferation causes excruciating pain and impairment. To cope with pain and manage symptoms and illness, pharmaceutical and non-pharmacological options are available. Self-care behaviors are recognized as a key source in symptom management and improving quality adherence to treatment among the current non-pharmacological strategies. The intervention measures to improve self-care were hardly impacted because of the narrow focus on physical self-care. Bringing in emotional self-care and addressing the individual's emotional health can enhance the effectiveness of interventions on a holistic level. Hence, this study has attempted to explore the factors that influence emotional self-care among individuals with cancer. Following an exploratory research design, the data were collected from 15 participants (4 men and 11 women) using purposive sampling and semi-structured interviews. Through thematic analysis, eight major themes were identified: physiological factors, social factors, family factors, psychological factors, individual factors, socioeconomic factors, cultural factors, and spiritual factors. The findings explained the emotional self-care among patients with cancer and how different identified factors influence their emotional self-care practices.